Learning from history: Lord Brain and Hashimoto's encephalopathy. Issue 4 (26th June 2019) - Crotty, Grace F; Doherty, Colin; Solomon, Isaac H; Berry, James D; Samuels, Martin A
Abstract : We present two historic cases of severe encephalopathy associated with antithyroid antibodies. The first was published by Lord Brain of Eynsham, and the second was from our department's archives. Although both cases are from archival sources, they continue to inform current clinical care. We briefly review the poorly defined entity, Hashimoto's encephalopathy, and discuss diagnostic advances for autoimmune encephalopathy and for Creutzfeldt-Jakob disease. We advocate for giving a trial of corticosteroids to patients with 'encephalopathy, not otherwise specified' while awaiting antibody results or more definitive testing. Our case, initially diagnosed as having Creutzfeldt-Jakob disease, responded remarkably (with video evidence) to a trial of corticosteroids.